Study of the process of management of the operating modes of electric networks in modern conditions - Бондаренко, Владимир Емельянович; Черемисин, Николай Михайлович; Черкашина, Вероника Викторовна (Eastern-European Journal of Enterprise Technologies, 2015)
To improve the process of management of operating modes of electric networks in modern conditions, the following tasks were solved. Technical and economic model of OL, taking into account the incompleteness of the initial information, which is characterized by changes in analytical connection of investments with the wire section to optimize the parametric series of wire sections was improved. The criterion of technical and economic distinctiveness of the OL options taking into account the discreteness of the scale of wire sections in forming the parametric series, which is a prerequisite for the OL unification and reduces the effect of network heterogeneity was formed. To optimize the process of management of electric power transmission, the principle of economic similarity in the problems of improving the OL structure based on unification, which provides a twofold extension of the object life until the first reconstruction at the minimum technological losses was elaborated. Some development aspects of OL as the active-adaptive objects of EN under the SmartGrid platform to regulate the process of management of electric power transmission in real time were presented.